2021
DOI: 10.1097/tp.0000000000003469
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Characteristics of Late Acute Antibody-mediated Rejection in Pediatric Liver Transplantation

Abstract: Background. An early and accurate diagnosis of liver antibody-mediated rejection (AMR) followed by timely intervention is important for clinical management but remains challenging. The aim of this study was to assess the clinicopathologic characteristics and outcomes of late acute AMR in pediatric liver transplantation recipients. Methods. We performed a retrospective review of 739 ABO-identical/compatible allograft liver biopsies from 199 pediatric tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
(56 reference statements)
1
6
0
Order By: Relevance
“…All but one of these patients received a DDLT graft, and none received a maternal‐LLD graft. Patient characteristics and histological findings of the patients with AMR have been previously described 26 . When we investigated the effect of post‐LT DSA on graft, patient, and ACR‐free survival, we did not detect any difference between positive and negative DSA patients (Figure S2).…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…All but one of these patients received a DDLT graft, and none received a maternal‐LLD graft. Patient characteristics and histological findings of the patients with AMR have been previously described 26 . When we investigated the effect of post‐LT DSA on graft, patient, and ACR‐free survival, we did not detect any difference between positive and negative DSA patients (Figure S2).…”
Section: Resultsmentioning
confidence: 67%
“…In the present study, 80% of children tested for post‐LT DSA were positive, which may represent a selection bias as they were likely being tested in the context of graft dysfunction or a rejection episode. Despite this high rate, AMR was diagnosed in only three childrenl 26 . Musat et al showed that in the adult population, preformed DSA was associated with an increased risk of ACR; however, only 2 out of 109 patients (1.8%) developed a rejection episode that fulfills the criteria for an AMR diagnosis 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the histopathology picture of an acute injury, the complement fragment 4d (C4d) linear and granular vascular deposition (demonstrated through specific immunohistochemical or immunofluorescence stain) ( Fig. 3 ) and positive serum Donor-Specific Antibodies (DSA) are required criteria to obtain a definitive diagnosis 48 , 55 , 59 , 60 …”
Section: Pathologic Evaluation Of the Pediatric Transplanted Livermentioning
confidence: 99%
“… 11 As a result, surveillance biopsies performed after the first year after Tx can reveal fibrosis, antibody-mediated chronic allograft injury; this can be with or without cellular infiltrates and circulating donor-specific antibodies. 12 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%